Cultural Heritage Based Marketing Mix in Majapahit Bejijong Village, Trowulan, Mojokerto, East Java - Ilmiatus Sholikhah; Ni Ketut Arismayanti; Ni Made Sofia Wijaya (Cita Konsultindo Research Center, 2024)
The tourism industry continues to grow at increasingly higher levels of competition, so marketing is needed. The Bejijong Majapahit Village Tourism Village, which has several tourist attractions in the form of Majapahit Kingdom heritage, such as Brahu Temple, Siti Inggil, Majapahit Village, and Majapahit Maha Vihara, cannot be separated from marketing activities. Several efforts have been made to become ADWI 2021 champion in the CHSE category, and comparative studies and promotions via social media have also been carried out, but more is needed to increase the number of visits and win the competition. Therefore, this research analyzes the appropriate marketing strategy for the Kampung Majapahit Bejijong Tourism Village. The approach used in this research is a mixed method. The respondents were 112 tourists and 12 experts. Data was analyzed using the Ifas and Efas, IE, and SWOT Matrix. The research results show that the marketing strategy that can be implemented is the S-O strategy, namely strengthening storytelling branding, organizing Majapahit Kingdom art performances, designing cultural preservation tourism activities, and creating exhibitions of local community crafts at historical sites. W-O's strategy is to conduct podcasts, create digital documentaries of the life of the Majapahit Kingdom era, provide Majapahit traditional clothing rentals, and create Majapahit trail activities. S-T's strategy was to add an audioguide and narrate the sacredness of the mojo tree. W-T's strategy is collaborating with sponsorship events and increasing authentic tourist attractions.